(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Pig diarrhea is a common problem in pig farms and scattered areas of Bangladesh. This study was subjected to characterize Escherichia coli isolated from fecal sample of pig diarrhea and to find out therapeutic possibilities in the treatment of the disease. Isolation and characterization of the microorganisms were confirmed on the basis of their morphology, staining, cultural and biochemical properties. The study was conducted on 125 fecal samples of diarrheic pig. The prevalence of E. coli infection was higher in 2 years and above aged pigs (62.50 %). Prevalence of E. coli was higher in diarrheic pigs 61.00 % (100) and non diarrheic 32.00% (25) were also found to be positive for E. coli. The results of MR and Indole test of E. coli isolates were positive. The antibiogram study revealed that this isolates were highly sensitive to ciprofloxacin, levofloxacin and gentamicin; moderately sensitive to colistin sulphate and azithromycin; less sensitive to amoxicillin, tetracycline, cloxacillin, ceftraexon, neomycin, erythromycin and ampicillin. The findinings of the experiment indicates that the use of ciprofloxacin, levofloxacin and gentamicin may have the preference to be choice in clinical control of E. coli causing pig diarrhea. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 31-36